HOW TEACHERS TEACH AND HOW STUDENTS PERCEIVE:TEACHING WRITING DESCRIPTIVE TEXTS USING STAD TECHNIQUE :A Quasi-Experimental Study of the Second Grade Students at one SMP in Bandung - Ferra Wulandari Dwi Sukmana, - (2012)
This research is intended to find out the implementation of Students Teams Achievement Division (STAD) technique in teaching writing descriptive text and to investigate the students' perception towards the implementation of STAD technique in writing class. This study employs a quasi experimental study involving 72 students of eighth grader of a Junior High School in Bandung. The instruments used in this research are tests (pretest and posttest) in writing descriptive text given to experimental and control group, and questionnaires given to experimental group. To answer the first question, data gained from posttest which is analyzed using t-test to identify whether there is a significant difference between the test scores of both experimental and control groups. Regarding the second question, the questionnaire data is presented to describe their opinion about the effect of this technique. The result of this study shows that: 1) STAD can help students to develop their writing performance. The statistical computation shows that STAD technique is likely effective in improving the students' writing performance in descriptive text (tobt 6.171 > tcrit 2.000, df=70). 2)Overall, students' perception toward the implementation of STAD is positive. The students regard that STAD has been helpful for them, such as encourage them to discuss, share students' opinion, increase students' writing skill in descriptive text particularly and enhance better relationship. Based on the findings, it is recommended that, teachers in Junior High School implement STAD technique in teaching various text types. Moreover, for further research, it is suggested to conduct the research on the implementation of various models of cooperative learning in developing other language skills.